1998
DOI: 10.1021/jm9708543
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV Agents That Selectively Target Retroviral Nucleocapsid Protein Zinc Fingers without Affecting Cellular Zinc Finger Proteins

Abstract: Agents that target the two highly conserved Zn fingers of the human immunodeficiency virus (HIV) nucleocapsid p7 (NCp7) protein are under development as antivirals. These agents covalently modify Zn-coordinating cysteine thiolates of the fingers, causing Zn ejection, loss of native protein structure and nucleic acid binding capacity, and disruption of virus replication. Concentrations of three antiviral agents that promoted in vitro Zn ejection from NCp7 and inhibited HIV replication did not impact the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
153
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(158 citation statements)
references
References 64 publications
(106 reference statements)
5
153
0
Order By: Relevance
“…Our results provide direct evidence of this differential zinc ejection. The greater reactivity of the carboxyl-terminal zinc finger toward attack by a variety of electrophiles has been attributed to a combination of steric factors and differences in nucleophilicity of the cysteines (22)(23)(24). Molecular modeling studies based on density-functional theory suggested that the thiolate of Cys 49 is the most electron rich and the most reactive toward highly polarizable electrophiles (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results provide direct evidence of this differential zinc ejection. The greater reactivity of the carboxyl-terminal zinc finger toward attack by a variety of electrophiles has been attributed to a combination of steric factors and differences in nucleophilicity of the cysteines (22)(23)(24). Molecular modeling studies based on density-functional theory suggested that the thiolate of Cys 49 is the most electron rich and the most reactive toward highly polarizable electrophiles (23).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular modeling studies based on density-functional theory suggested that the thiolate of Cys 49 is the most electron rich and the most reactive toward highly polarizable electrophiles (23). Molecular modeling studies show that the reactive sites of the carboxyl-terminal zinc finger lie in a more contiguous reactive surface compared with the amino-terminal finger (24). Docking of some antiviral agents, 2,2Ј-dithiobis(benzamide) disulfides-1 in particular, revealed that the structure of the carboxyl-terminal finger allows a significantly closer approach of the ligands to the cysteine thiolates, compared with the amino-terminal finger (24).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] This process involves interaction between the gag nucleocapsid protein p7 (NCp7) and a region of the HIV genome known as the packaging signal (Κ). This interaction is an attractive target for antiviral therapy because the secondary structures of Κ and nucleocapsid are highly conserved among retroviruses [5][6][7][8][9] and mutations in NCp7 result in totally defective virions. [10][11][12] This suggests that drug resistance to "packaging inhibitors" is less likely to develop.…”
Section: Introductionmentioning
confidence: 99%
“…They can target the residues that coordinate the zinc ions, to a greater (Cys-49, Cys-36) or lesser (Cys-39) extent (25). Several studies proved that some compounds can have high selectivity for the CCHC zinc finger-type found only in retroviruses and a very few cellular proteins, such as poly(ADP-ribose) polymerase (26). However, the zinc ejector agents are still avoided because of their potential cytotoxicity at high concentrations.…”
Section: Introductionmentioning
confidence: 99%